Introduction and Removal of Disinfection Byproducts and Mutagenic Activity by Chemical and Photolytic Treatments - Backlund, P. (Revue des sciences de l'eau / Journal of Water Science, 1995)
Samples from four different raw water sources were treated with various disinfectants and subjected to chemical analyses and mutagenicity assays. The following disinfectants were used: chlorine (Cl2), chlorine dioxide (ClO2), monochloramine (NH2Cl), ozone (O3), ultraviolet radiation (UV), and combinations of Cl2/ClO2, O3/Cl2, UV/Cl2, and UV/O3/Cl2. The samples were analysed for adsorbable organic halogens (AOX), chloroform (CHCl3), carboxylic acids, volatile organics, chlorite, the strong mutagen 3-chloro-4 (dichloromethyl)-5-hydroxy-2 (5H)-furanone (MX), and mutagenic activity (as detected by the Ames test).Humic lake water which had been treated with the combination UV/Cl2 exhibited a higher level of mutagenicity and higher concentrations of MX and CHCl3 than water treated with Cl2 alone. The same observation was made for the mutagenicity and the CHCl3 concentration in waters preoxidized with low doses of O3 and UV/O3, respectively. When higher doses of these powerful oxidants were used in the pretreatment step, the level of mutagenicity, MX and CHCI3 were lower than in water chlorinated without pretreatment. The combination UV/O3 was found to be more efficient than O3 alone in destroying the precursor material to the mutagenic compounds and chloroform.The higher the proportion of ClO2 in the combined Cl2/ClO2 process, the lower the levels of mutagenicity, MX, CHCl3, and AOX. The production of inorganic chlorite increased with a higher proportion of ClO2.Aldehydes, n-alkanes, and low molecular-weight carboxylic acids were identified as byproducts following UV treatment of humic lake water.The mutagenic activity (per amount of DOC) was approximately similar after chlorination of humic rich surface- and ground waters as after chlorination of waters from the rivers Meuse and Rhine, containing relatively low amounts of humic matter. The precursors to MX were found to be more abundant in the humic waters than in the river waters.